Body composition and bone mineral density by Dual Energy X-ray Absorptiometry: Reference values for young children. Issue 1 (January 2022) - van Beijsterveldt, Inge A.L.P.; van der Steen, Manouk; de Fluiter, Kirsten S.; Spaans, Sander A.M.J.; Hokken-Koelega, Anita C.S.
Summary: Background & aims: Childhood obesity is a global public health threat, with an alarming rise in incidence. Obesity at young age has short-term and long-term morbidity. It is, therefore, important to accurately assess body composition throughout infancy and childhood to identify excess adiposity. However, reference values for age 2–5 years, needed to interpret measurements and identify young children at risk, are lacking. Our primary objective was to fill the current gap in reference values by constructing sex-specific body composition reference values and charts for fat mass (FM), fat mass percentage (FM%), fat mass index (FMI), lean body mass (LBM), lean body mass index (LBMI) and total body less head bone mineral density (BMDTBLH ) for children aged 2–5 years using Dual-Energy X-ray Absorptiometry (DXA). Methods: We performed 599 accurate DXA-measurements in 340 term-born children aged 2–5 years, using Lunar Prodigy with Encore software (V14.1). Using GAMLSS, sex-specific reference values and charts were created for FM, FM%, FMI, LBM, LBMI and BMDTBLH . Results: Sex-specific body composition reference values and charts for age 2–5 years were constructed. In boys and girls, FM and LBM increased from age 2–5 years (all p ≤ 0.001), but body size-corrected FM% and FMI decreased (all p ≤ 0.023). LBMI remained similar between 2 and 5 years of age. Girls had higher FM, FM% and FMI and lower LBM and LBMI compared to boys. BMC and BMDTBLH increased with age between 2 and 5 years of age (all p < 0.001) and were similar for boys and girls. Conclusions: We present sex-specific reference values and charts for body composition and total body bone mineral density measured by DXA, based on a large cohort of healthy children aged 2–5 years. These longitudinal references can be used for clinical practice and research purposes to monitor body composition and bone mineral density development and identify children at risk for excess adiposity.